Monocytosis as a Prognostic Factor in Idiopathic Pulmonary Fibrosis - Haider, Waseem; Ali Sajjad, Malik Istikhar; Abbas, Muhammad Naveed; Khalid, Usman; Saif ur Rahman; Aqil, Mehvish (Indus Journal of Bioscience Research, 2025)
Objective: To determine increased monocyte, count (monocytosis) as a cellular biomarker for poor outcomes in idiopathic pulmonary fibrosis METHODS: A descriptive cross-sectional study was conducted at Allied Hospital-2, Faisalabad. A total of 305 patients aged 30–70 years with confirmed IPF were enrolled using non-probability consecutive sampling. Monocyte counts were classified into three groups: Group I (